Generalized Green's matrix for linear pulse boundary-value problems - Karandzhulov, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We establish an algebraic criterion of solvability, study the structure of general solutions of linear boundary-value problems for systems of differential equations with pulse effects, and construct the generalized Green's matrix.